Gray Matter Structural Alterations in Social Anxiety Disorder: A Voxel-Based Meta-Analysis - Wang, Xiuli; Cheng, Bochao; Luo, Qiang; Qiu, Lihua; Wang, Song (Frontiers in Psychiatry, 2018)
The current insight into the neurobiological pathogenesis underlying social anxiety disorder (SAD) is still rather limited. We implemented a meta-analysis to explore the neuroanatomical basis of SAD. We undertook a systematic search of studies comparing grey matter volume (GMV) differences between SAD patients and healthy controls (HC) using a whole-brain voxel-based morphometry (VBM) approach. The anisotropic effect size version of seed-based d mapping (AES-SDM) meta-analysis was conducted to explore the GMV alterations of SAD patients compared with HC. We included eleven studies with 470 SAD patients and 522 HC in the current meta-analysis. In the main meta-analysis, relative to HC, SAD patients showed larger GMVs in the left precuneus, the right middle occipital gyrus (MOG) and supplementary motor area (SMA), as well as smaller GMV in the left putamen. In the subgroup analyses, compared with controls, adult patients with SAD exhibited larger GMVs in the left precuneus, the right superior frontal gyrus (SFG), angular gyrus, middle temporal gyrus (MTG), MOG and SMA , as well as smaller GMVs in the left thalamus; SAD patients without comorbid depressive disorder exhibited larger GMVs in the left superior parietal gyrus and precuneus, the right inferior temporal gyrus, fusiform gyrus, MTG and superior temporal gyrus (STG), as well as smaller GMVs in the bilateral thalamus; currently drug-free patients with SAD exhibited smaller GMV in the left thalamus compared with HC while no larger GMVs were found. For SAD patients with different clinical features, our study revealed directionally consistently greater cortical GMVs and smaller subcortical GMVs, including locationally consistently larger precuneus and thalamic deficit in the left brain. Age, comorbid depressive disorder and concomitant medication of patients might be the potential confounders of SAD at the neuroanatomical level.